Легенди та перекази кінця ХVI - початку ХVІІ ст. в записах Петра Могили - Іваннікова, Л. (Народна творчість та етнографія, 2008)
For the first time in the history of the Ukrainian folkloristics the author researches the records of legends made by sanctifier Petro Mohyla at the beginning of the 17th century mainly in Kyiv suburbs. The author focuses on authenticity of the texts, their links to the traditional legendry and hagiography as well as methods of recording.